GAMBARAN TINGKAT KEPUASAN SEKSUAL SUAMI-ISTRI DENGAN ISTRI MENJALANI PENGOBATAN KANKER SERVIKS - Ayu Fitri Suarlis; Yulia Irvani Dewi; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The purpose of this study was to determine the description of the level of sexual satisfaction husband andwife with wife undergoing treatment of cervical cancer. The study design was descriptive involving 30couples. The sampling method is accidental sampling. The measuring tool used is a questionnaire that hasbeen tested for validity and reliability. The analysis used is univariate analysis. The results of the researchbased on the characteristics of respondents showed that most of the respondents were elderly (60.0%),housewife (46.7%), primary school (35.0%), stage II (43,3%) , chemotherapy (46.6%). The level ofsatisfaction of majority wife is not satisfied (73,3%), and husband majority is not satisfied (63,3%). Theresults of this study recommend that nurses can perform sexual counseling for couples to enhance therelationship of intimacy (intimacy).Keywords: cervical cancer, sexual satisfaction, treatment.